Implementation of Access Arrangements for Agrarian Reform: A Case Study in the Kampung Tua of Tanjung Riau, Batam City - Yunirahma Saragih, Fratia; Chayati, Siti Noor; Wahyuni, Wahyuni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: Access arrangement is one of the agrarian reform programs that continues from asset arrangement. Access arrangements aim to provide assistance in capital provision, training, and marketing strategies to communities facing obstacles in their companies. In 2022, Kampung Tua Tanjung Riau served as the location for access arrangements; data collection yielded various types of Micro-Medium Small Businesses (MSMEs), also known as agrarian reform access objects. This study aims to find out how agrarian reform access is put into action in Kampung Tua Tanjung Riau. It will do this by using a qualitative approach and collecting data from the ground about the types of businesses that agrarian reform access participants run, the status of their businesses, the status of their certificates (mortgaged or not mortgaged), and how successful their businesses are by looking at how they've grown since being given more power and by mortgaging their land ownership certificates for extra business capital. There was an increase in the number of participants who pledged certification from 40 in 2022 to 53 in 2023. However, some of the participating businesses have not experienced significant development. The constraints in the implementation of the agrarian reform access arrangement in Kampung Tua Tanjung Riau are the lack of community understanding of the program, where not all participants are registered for empowerment training, and the abundance of similar businesses that are not balanced with existing market demands, resulting in competition among MSME players. Keywords: Agrarian Reform, Access Arrangement, Community Empowerment